Mengeksplorasi Praktik Manajemen Operasional pada UMKM Kreatif di Jakarta: Studi Kualitatif tentang Strategi Efisiensi - Fariha, Ainna Fariha; Runiti, Shinta Runiti (ICON Publisher, 2025)
This study explores how creative micro, small, and medium enterprises (MSMEs) in Jakarta manage their operations through adaptive and interpretive practices. Using a qualitative approach grounded in the interpretive paradigm, data were collected through in-depth interviews and observations with MSME owners and creative practitioners. The findings reveal that operational management in creative MSMEs relies on hybrid structures combining informal coordination, trust-based collaboration, and adaptive learning. Resource utilization is characterized by improvisation and relational capability, while operational adaptability reflects dynamic sensing and reconfiguration of processes. The integration of Operations Management Theory, Resource-Based View, and Dynamic Capabilities Theory provides a multidimensional lens to understand how creativity and efficiency coexist. The study concludes that operational effectiveness in creative MSMEs emerges from the interplay of structure, resource orchestration, and adaptability, sustained by socio-cultural embeddedness and digital transformation. The research contributes to theoretical enrichment in operations management and offers practical implications for policymakers and entrepreneurs seeking to strengthen the creative economy in emerging markets.